2013
DOI: 10.4208/cicp.401011.220212s
|View full text |Cite
|
Sign up to set email alerts
|

Extended BGK Boltzmann for Dense Gases

Abstract: An alternate BGK type formulation of the Enskog equation has been recently proposed. It was shown that the new model has a valid H-theorem and correct thermal conductivity. We propose Lattice Boltzmann (LB) formulation of this new Enskog-BGK model. The molecular nature of the model is verified in case of shear flow by comparing the predicted normal stress behavior by the current model with the prediction of molecular dynamics simulations. We extend the model for multiphase flow by incorporating attractive part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…When ρ l and ρ g are given, the viscosity ratio υ g /υ l will be determined. Following the molecular theory, in the LB community Suryanarayanan et al [51] have adopted a variable viscosity ratio for simulating dense gases. In the present work, in order to investigate the effect of the viscosity ratio on the pseudopotential LB model, we employ various values of υ g /υ l for given ρ l and ρ g , and it is found that a lower liquid kinematic viscosity can be gained with the increase of υ g /υ l .…”
Section: Droplet Splashing On a Thin Liquid Filmmentioning
confidence: 99%
“…When ρ l and ρ g are given, the viscosity ratio υ g /υ l will be determined. Following the molecular theory, in the LB community Suryanarayanan et al [51] have adopted a variable viscosity ratio for simulating dense gases. In the present work, in order to investigate the effect of the viscosity ratio on the pseudopotential LB model, we employ various values of υ g /υ l for given ρ l and ρ g , and it is found that a lower liquid kinematic viscosity can be gained with the increase of υ g /υ l .…”
Section: Droplet Splashing On a Thin Liquid Filmmentioning
confidence: 99%
“…The above model of free-energy is the simplest model that gives two stable phases provided F has two minima and was first formulated by van der Waals [72]. The macroscopic mass and momentum conservation equations are given by [74,75]…”
Section: Nonideal Fluids and Two-phase Flowmentioning
confidence: 99%
“…The above form of g nid α , known as the pressure formulation, is sufficient to incorporate the nonideal interactions and the Korteweg's stress tensor in the lattice Boltzmann model [40,69,74]. Alternatively, by exploiting the Gibbs-Duhem relation one can write the chemical potential formulation as [69,75]…”
Section: Nonideal Fluids and Two-phase Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo (1998), He et al (1998), Wang et al (2020), Su et al (2023) and Busuioc (2023). Based on the intuitive observations of the underlying molecular physics, various types of simple kinetic models (Suryanarayanan, Singh & Ansumali 2013;Takata & Noguchi 2018;Takata, Matsumoto & Hattori 2021) have been developed for the van der Waals fluids, which have been applied successfully to the study of phase transition problems. However, these models are either limited to the low-speed/isothermal flows or fail to reproduce the correct transport coefficients.…”
Section: Introductionmentioning
confidence: 99%